Chemical cross linking modification of matrimid membranes using phenylenediamine for gas separation - Farhana Aziz, 1984-, author; Ahmad Fauzi Ismail, 1966-, author; International Conference on Membrane Science & Technology (7th: 2009: Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL